2023
DOI: 10.36660/abc.20220679
|View full text |Cite
|
Sign up to set email alerts
|

Investigação da Relação entre Índice de Triglicerídeos-Glicose e Fluxo Lento Coronariano: Um Estudo Retrospectivo de Caso-Controle

Abstract: Resumo Fundamento O fluxo lento coronariano (FLC) refere-se à opacificação retardada dos vasos distais na ausência de estenose da artéria coronária epicárdica. O mecanismo etiopatogênico do FLC ainda não está claro. Objetivos Este estudo investiga a relação entre o FLC e o índice de triglicerídeos-glicose (TyG). Métodos A amostra do estudo consistiu de 118 pacientes com FLC e 105 pacientes com fluxo coronariano normal (FCN). A ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…3 The investigation of the relationship between TyGI and coronary slow flow (CSF) could be of great interest in clinical practice, as studies have demonstrated a strong association between IR and CSF, considering IR as an independent risk factor for CSF in patients with IGT. 4,5 Arterial stiffness is one of the earliest types of functional damage that occurs during the vascular aging process, during which arterial elasticity decreases. 6 Growing evidence suggests that arterial stiffness is a powerful predictor for future risk of CVDs such as acute coronary syndromes, heart failure, and ischemic or hemorrhagic stroke.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 The investigation of the relationship between TyGI and coronary slow flow (CSF) could be of great interest in clinical practice, as studies have demonstrated a strong association between IR and CSF, considering IR as an independent risk factor for CSF in patients with IGT. 4,5 Arterial stiffness is one of the earliest types of functional damage that occurs during the vascular aging process, during which arterial elasticity decreases. 6 Growing evidence suggests that arterial stiffness is a powerful predictor for future risk of CVDs such as acute coronary syndromes, heart failure, and ischemic or hemorrhagic stroke.…”
mentioning
confidence: 99%
“…A investigação da relação entre TyGİ e fluxo lento coronariano (FLC) pode ser de grande interesse na prática clínica, pois estudos têm demonstrado forte associação entre RI e FLC, considerando a RI como fator de risco independente para FLC em pacientes com diagnóstico de intolerância à glicose. 4 , 5 …”
unclassified
See 1 more Smart Citation